Online VLSM IP calculator - Mohd Azuwan, Efendy Mail (2010)
Online VLSM Calculator is a system that has a useful function to the FCSSE. The user of this system is Faculty of Computer Systems and Software Engineering, staff and student of University Malaysia Pahang, and anyone who want to use this system. This system has been developing based on the research that has been made at the FCSSE. Before this student and staff in FCSSE has to calculate the IP address manually. It difficult for the staff and student to calculate the IP. That is the main reason why this system has been develops. The solution that has been made to solve the problem is by providing the correct answer for the user. This system was developed using the Dreamweaver, Javascript and Adobe Photoshop. This system will successful develop according to the propose objective in chapter one. For further used hope this system will be used for all networking comity and can be more users friendly.